Penerapan Alat Bantu Pengaduk dan Manajemen Rantai Pasok untuk UMKM Pembuat Rendang - Libyawati, Wina; Mahandika, Dhidik Mahandika; Pane, Erlanda Augupta; Usman, Yulita Veranda Usman (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2023)
This community service program aims to solve the unstandardized production process and the high bargaining power from suppliers in rendang making for Small, Micro, and Medium Businesses (MSMEs). The appropriate technology and consultation training implementation are the applied method in achieving the goal. Therefore, the main problems to be solved are uniformity mixture between seasoning and meat during cooking process within 4-5 hours and low management skill to organize the supply chain components. The results are a uniform mixture of all ingredients and SMMB has basic supply chain management skills. The stirring process with constant speed and intermittent monitoring process during the entire cooking process produces the uniformity mixture. The SMMB is equipped with the skill to identify the supply chain components in the form of compact map. This community service program can blend technology and management implementation into interconnected activities to increase the MSMEs competitiveness, unlike similar community service program.